Resolving a century-old year mystery – the identity and provenance of the semiterrestrial crab, Parathelphusa (Liothelphusa) nobilii Colosi, 1920 (Decapoda, Brachyura, Gecarcinucidae) from Sarawak and a replacement name for Parathelphusa nobilii Ng, 2014 - Peter K. L., Ng; Jongkar, Grinang (Pensoft Publishers, 2026)
The uncertain taxonomic identity and provenance of the gecarcinucid karst crab Parathelphusa (Liothelphusa) nobilii Colosi, 1920 is resolved through the examination of historical type material and newly collected specimens. Stygothelphusa nobilii (Colosi, 1920) is confirmed as a distinct species closely related to S. bidiensis Lanchester, 1900, but it can be easily distinguished by its more quadrate carapace, the anterolateral margin being armed with a low epibranchial tooth, proportionally shorter ambulatory legs, and diagnostic gonopod morphology. The originally stated type locality, “Mt Saribau” is considered erroneous. Evidence from the collector’s records and recent collections indicate that the species was very likely obtained from the limestone karsts around Gua Chupak in southwestern Sarawak. In addition, Parathelphusa nobilii Ng, 2014 from Sambas in Indonesian Kalimantan is identified a junior primary homonym of Parathelphusa (Liothelphusa) nobilii Colosi, 1920. A replacement name, P. daisyae nom. nov., is therefore proposed.